1991
DOI: 10.1073/pnas.88.14.6333
|View full text |Cite
|
Sign up to set email alerts
|

Diverse point mutations in the human gene for polymorphic N-acetyltransferase.

Abstract: Classification of humans as rapid or slow acetylators is based on hereditary differences in rates of N-acetylation of therapeutic and carcinogenic agents, but N-acetylation of certain arylamine drugs displays no genetic variation. Two highly homologous human genes for N-acetyltransferase (NAT; arylamine acetyltransferase, acetylCoA:arylamine N-acetyltransferase, EC 2.3.1.5), NAT] and NAT2, presumably code for the genetically invariant and variant NAT proteins, respectively. In the present investigation, 1.9-ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
72
0
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(74 citation statements)
references
References 16 publications
1
72
0
1
Order By: Relevance
“…Subsequent study revealed that this allele has the same three nucleotide substitutions i.e. nt (nucleotide position according to Ohsako and Deguchi (1990)) 341,481, and 803 as ra reported recently by Vatsis et al (1991) (manuscript in preparation). Allele 4 is referred to as a 'slow' type allele (Vatsis et al, 1991).…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…Subsequent study revealed that this allele has the same three nucleotide substitutions i.e. nt (nucleotide position according to Ohsako and Deguchi (1990)) 341,481, and 803 as ra reported recently by Vatsis et al (1991) (manuscript in preparation). Allele 4 is referred to as a 'slow' type allele (Vatsis et al, 1991).…”
Section: Introductionsupporting
confidence: 60%
“…nt (nucleotide position according to Ohsako and Deguchi (1990)) 341,481, and 803 as ra reported recently by Vatsis et al (1991) (manuscript in preparation). Allele 4 is referred to as a 'slow' type allele (Vatsis et al, 1991). Consequently Nacetylator phenotypes can be predicted by determining which combination of the 4 known alleles an individual has.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…NAT1 and NAT2 are products of single, intronless exons containing single 870 bp open-reading frames encoding 290 amino acids (Blum et al, 1991;Vatsis et al, 1991). NAT1, NAT2 and a pseudogene NATP are located on the short arm of human chromosome 8 NAT2 polymorphism and urinary bladder cancer risk DW Hein (Blum et al, 1990;Hickman et al, 1994) in the orientation NAT1:NATP:NAT2 (Matas et al, 1997).…”
Section: Molecular Geneticsmentioning
confidence: 99%
“…One of the alleles confers the fastacetylator type, whereas the other alleles are associated with slow acetylation (Vatsis et al, 1991;Hickman et al, 1992). The AAC-I locus encodes what has been considered as monomorphic N-acetyltransferase (NAT).…”
Section: Introductionmentioning
confidence: 99%